Real-Time Feedback in Swimming Exercises Using Embedded Devices in Water - Vladut-Alexandru Dobra; Ionut-Marian Dobra; Silviu Folea; Radu Sabau (Applied Sciences, 2025)
Wearable devices are gaining prominence in a variety of applications, including athletic and physical activity monitoring. Their effectiveness often relies on the ability to deliver instantaneous feedback, enabling timely responses and supporting their integration into fast-paced, interactive contexts. Based on these aspects, this paper proposes a wearable system that collects accelerometer and gyroscope data using the MPU6050 sensor from three points on a human arm. The collected data are compared to a predefined set of values using Dynamic Time Warping. Each wearable device provides live feedback via a vibration motor if a stroke deviates from the desired motion. The entire system enables swimming coaches to monitor individual strokes in real time using Wi-Fi connectivity while also allowing athletes to receive immediate feedback when their strokes are executed incorrectly. This system aids in identifying improper swimming techniques and enables faster correction, ultimately improving performance. Experiments will be performed in water environment supervised by a specialized swimming coach.